Peran Suku Bunga dalam Memperkuat atau Melemahkan Pengaruh Tax Planning dan Financial Distress terhadap Nilai Perusahaan - Irlenda Octaviani Torada; Wenten, I Ketut (Jurnal Ekonomi Manajemen Akuntansi, 2026)
This study aims to examine and analyze the role of interest rates in strengthening or weakening the effect of Tax Planning and Financial Distress on Firm Value. This research employs a quantitative approach. The population of this study consists of consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024, totaling 128 companies. The research sample was selected using purposive sampling, resulting in 42 companies that met the specified criteria, with a total of 210 observations. Panel Data Linear Regression Analysis and Moderated Regression Analysis (MRA) were conducted using Microsoft Excel and E-Views version 12. The results indicate that Tax Planning has no significant effect on Firm Value, while Financial Distress has a significant effect on Firm Value. Regarding the moderating variable, the interest rate is unable to strengthen or weaken the effect of Tax Planning on Firm Value; however, Interest Rates are able to moderate (weaken) the effect of Financial Distress on Firm Value.